1997
DOI: 10.1074/jbc.272.33.20660
|View full text |Cite
|
Sign up to set email alerts
|

Human Phospholipase D1 Can Be Tyrosine-phosphorylated in HL-60 Granulocytes

Abstract: The human phospholipase D1 (hPLD1) has recently been cloned. Although recent data have implicated PLD in receptor-stimulated secretion, the regulation of the activity of PLD enzymes remains to be clarified. Purified hPLD1 is activated by several cytosolic cofactors among which are protein kinase C␣, ARF, and RhoA. In human granulocytes, a strong correlation between tyrosine phosphorylation of proteins and PLD activity has been established. In this study, the presence of hPLD1 in HL-60 granulocytes and its phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 29 publications
3
72
0
Order By: Relevance
“…In HL-60 granulocytes, the isoform PLD1 is tyrosyl phosphorylated in response to peroxides of vanadate [19]. In Swiss 3T3 fibroblasts, hydrogen peroxide induces PLD1 activation via protein tyrosine kinases [20].…”
Section: Introductionmentioning
confidence: 99%
“…In HL-60 granulocytes, the isoform PLD1 is tyrosyl phosphorylated in response to peroxides of vanadate [19]. In Swiss 3T3 fibroblasts, hydrogen peroxide induces PLD1 activation via protein tyrosine kinases [20].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 has been reported to enhance tyrosine phosphorylation of the platelet-derived growth factor (PDGF) receptor, the epidermal growth factor receptor, Src kinase, and mitogen-activated protein kinase, leading to activation of gene expression including c-fos, c-myc, c-jun, NF-B, and AP-1 (12)(13)(14)(15)(16). Tyrosine phosphorylation has also been implicated in PLD activation mediated by epidermal growth factor (17), PDGF (18), pervanadate (19,20), fMet-Leu-Phe (21), and immunoglobulin E (22). Furthermore, inhibitors of protein-tyrosine phosphatases such as peroxides of vanadate stimulate PLD activity by G proteinindependent (19) and -dependent (23) mechanisms.…”
mentioning
confidence: 99%
“…Furthermore, inhibitors of protein-tyrosine phosphatases such as peroxides of vanadate stimulate PLD activity by G proteinindependent (19) and -dependent (23) mechanisms. Recently, it was reported that, in response to stimulation by peroxides of vanadate, human brain PLD1 was tyrosine-phosphorylated and associated with several undefined, tyrosine-phosphorylated proteins in HL-60 cells (20).…”
mentioning
confidence: 99%
“…Indeed, although the tyrosine kinase inhibitors ST-638, MDHC and genistein inhibit fMLP-induced PLD activation, we were unable to detect tyrosine phosphorylation of hPLD1 in fMLPstimulated granulocytes (data not shown). Furthermore, a small fraction of total PLD1 was found tyrosine phosphorylated after a 10-min stimulation with V 4ϩ -OOH [30]. Finally, the time course of PLD activation and tyrosine phosphorylation of PLD1 elicited by V 4ϩ -OOH were not similar, with PLD activation preceding tyrosine phosphorylation of hPLD1 by several minutes [14,30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a small fraction of total PLD1 was found tyrosine phosphorylated after a 10-min stimulation with V 4ϩ -OOH [30]. Finally, the time course of PLD activation and tyrosine phosphorylation of PLD1 elicited by V 4ϩ -OOH were not similar, with PLD activation preceding tyrosine phosphorylation of hPLD1 by several minutes [14,30].…”
Section: Discussionmentioning
confidence: 99%